Development of the Aboriginal Communication Assessment After Brain Injury (ACAABI): A screening tool for identifying acquired communication disorders in Aboriginal Australians. (4th May 2017) - Armstrong, Elizabeth M; Ciccone, Natalie; Hersh, Deborah; Katzenellebogen, Judith; Coffin, Juli; Thompson, Sandra; Flicker, Leon; Hayward, Colleen; Woods, Deborah; McAllister, Meaghan
Abstract: Purpose : Acquired communication disorders (ACD), following stroke and traumatic brain injury, may not be correctly identified in Aboriginal Australians due to a lack of linguistically and culturally appropriate assessment tools. Within this paper we explore key issues that were considered in the development of the Aboriginal Communication Assessment After Brain Injury (ACAABI) – a screening tool designed to assess the presence of ACD in Aboriginal populations. Method : A literature review and consultation with key stakeholders were undertaken to explore directions needed to develop a new tool, based on existing tools and recommendations for future developments. Result : The literature searches revealed no existing screening tool for ACD in these populations, but identified tools in the areas of cognition and social-emotional wellbeing. Articles retrieved described details of the content and style of these tools, with recommendations for the development and administration of a new tool. The findings from the interview and focus group views were consistent with the approach recommended in the literature. Conclusions : There is a need for a screening tool for ACD to be developed but any tool must be informed by knowledge of Aboriginal language, culture and community input in order to be acceptable and valid.